The Effect of Learning Strategies and Creative Thinking Ability on Learning Outcomes of Islamic Religious Education - Ida Nurhayati; Khaerudin Khaerudin; Moh. Sukardjo (Peneliti.net, 2020)
This study aims to determine: the learning outcomes of Islamic Religious Education students who are taught withlearning strategies Problem Based Learning and students who are taught withlearning strategies Contextuan Teaching Learning; learning outcomes of Islamic Religious Education students who have high creative thinking skills with students who have low creative thinking skills; know the interaction of the use of learning strategies with the ability to think creatively in influencing the learning outcomes of Islamic Religious Education. The research method used is a quasi-experimental. The test results show: the learning outcomes of students taught by thelearning strategy Problem Based Learning are higher than students who are taught with thestrategy Contextuan Teaching Learning; the learning outcomes of Islamic Religious Education students with high creative thinking abilities are higher than students with low creative thinking abilities; and there is an interaction between learning strategies and the ability to think creatively on learning outcomes of Islamic Religious Education. To improve learning outcomes of Islamic Religious Education for students at SMK Negeri 1 Setu Bekasi Regency who have high creative thinking abilities can be done by usinglearning strategies Problem Based Learning, on the other hand for students who have low creative thinking abilities it can be done withlearning strategies Contextuan Teaching Learning, In general, to improve the learning outcomes of Islamic Religious Education students of SMK Negeri 1 Setu Bekasi Regency can be done by using thelearning strategy Problem Based Learning